Applying Antconc in Regex Search on BBC News Text - Harahap, Annisah Inriani; Samuel Nugraha Cristy; Sultan Salma Efendi; Tengku Silvana Sinar (TALENTA, 2024)
The software AntConc has become a freeware and multi-platform tool used in corpus-based linguistic research. Corpus linguistics itself is identified as a methodology consisting of various related methods that can be used by scholars with different theoretical tendencies. This research aims to determine the formulas used in searching regular expressions in news articles. The news data was collected from a known media source called BBC News. The research results indicate that Regex in Antconc can be performed in various ways, including: (1) To find words starting with 'sp,' the formula ^sp[a-z] can be used, (2) To find words starting with 'st' and ending with 'ed,' the formula ^st[a-z]*ed can be used, (3) To find words ending with '-ing,' the formula [a-z]*ing can be used, (4) To find a phrase containing two words, with the first word starting with the letter 's' and the second word starting with the letter 't,' the formula ^s[a-z] ^t[a-z] can be used.